(3MjGI GdMjhGfs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s ((3SQjGbhS s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa fhY GdEfSGf , HGdCUZQjf GdbdH hGddSGf hHYO agPG hEfeG OYGfi Edi Pdc Cfg hbY hESJNQJ Gddg ai hVY cJGH SejJg MjGI GdMjhGf s
(3BNQgG (B:s
(3BNQg ai GdcdGe Ydi CHj RjGO(B" (3ef BNQ MQa GdRGi (B:" (3bGd g ai GdeQUY Edi gfG fUa GdcJGH s
(3GdfSNI HgG MhGTs
(3GdfUa GdChd ef fSNI CNQis
(3YdjgG eWGdYI HGSe eMeO Hf YHO Gddg GdHdbjfi GdMfais
(3cJHJ CSeGA GdMjhGfGJ ajgG HGdMeQI s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3GdeYGQa GdYGeIs